A numerical misinterpretation in the computer screen during middle of the image free navigation assisted knee replacement-a dilemma of what to do next? - Selvanayagam, Rajkumar; Pfluger, Gerald (International Journal of Research in Medical Sciences, 2017)
Misinterpretation can occur during any step of navigation system. It is not only a dilemma for the orthopaedic surgeons on how to proceed further in such instances, but also a challenging situation to take a right call. We report here an unusual error encountered in image free Orthopilot navigation system during knee replacement surgery. A gross numerical measurement error occurred in the computer screen while femoral planning step in the tibia first technique, following which a dilemma persisted on how to proceed further. The system was reverted backwards, and the procedure was initiated again right from the beginning of the registration of bony landmarks, followed by completion of all other consecutive steps with the help of navigation system. The end result of the surgery was achieved at an accurate neutral mechanical axis with 5 degrees of maximum possible extension.